2021
DOI: 10.1108/emjb-03-2021-0036
|View full text |Cite
|
Sign up to set email alerts
|

Investigating digital storytelling for the creation of positively engaging digital content

Abstract: PurposeThis study explores how digital storytelling (DST) approaches can be used for social media campaigns to create more engaging digital content. The ability to better engage with networked publics offers benefits to entities of different scale and scope, since in doing so they establish stronger relationships with their consumers and publics.Design/methodology/approachA digital discourse analysis combined with a five-layer coded film analysis is applied to a DST video, viewed on Facebook.FindingsFour overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 44 publications
(58 reference statements)
0
15
0
2
Order By: Relevance
“…It is important to offer new educational techniques based on the use of digital technology in order to foster the development of meaningful learning [53]. Active participation and 21st-century teaching and learning are now possible thanks to modern collaborative technology, such as digital storytelling [48]. There are numerous ways that digital storytelling may be used in education, and one of the most important considerations to make when incorporating this device into the curriculum is whether teachers are well equipped and prepare to use digital stories [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to offer new educational techniques based on the use of digital technology in order to foster the development of meaningful learning [53]. Active participation and 21st-century teaching and learning are now possible thanks to modern collaborative technology, such as digital storytelling [48]. There are numerous ways that digital storytelling may be used in education, and one of the most important considerations to make when incorporating this device into the curriculum is whether teachers are well equipped and prepare to use digital stories [16].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, students will try to personalise their story by recording themselves and reciting the script, and this involves the students training themselves to become more confident with their speech, and this improves their speaking skills as well [15]. Research shows that new technologies have given presence to the digital storytelling method, and this has paved the way for educators and policymakers to enhance the learning process, especially when it comes to improving the ability of students to speak effectively [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sin embargo, generar un compromiso positivo a través de las plataformas de redes sociales, sigue siendo uno de los desafíos más difíciles para los estrategas y gerentes de redes sociales. Nicoli, et al (2021) señalan como la narración de historias es ampliamente considerada como el principal método para dar sentido al mundo y el centro de la construcción de significado humano. Las historias son una forma efectiva de transmitir información y valores de un individuo o comunidad a la siguiente.…”
Section: Transmisión De Valoresunclassified
“…The popularity of digital storytelling applications such as WhatsApp, Instagram, Snapchat and TikTok has resulted in their implementation in language learning activities which foster the development of multiliteracies. In fact, it has been demonstrated that by integrating virtual narrations with multimedia components and web publishing technologies, digital storytelling platforms are likely to encourage students' active learning and collaboration towards content creation (Tahriri, Tous, MovahedFar 2017;Nicoli et al 2021). From a linguistic point of view, studies have shown that the use of digital storytelling platforms can improve learners' interactions and pronunciation skills, as well as target language use outside of classroom walls (Nuraeni, Nurmalia 2020;Yang 2020;Tragant et al 2021).…”
mentioning
confidence: 99%